DEVELOPMENT OF CHILDREN’S SPEECH OF JUNIOR SCHOOL AGE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This topic focuses on the development of children's speech during the junior school age, typically between the ages of 6 to 10 years. The annotation provides an overview of the factors influencing speech development during this critical period, including cognitive, social, and linguistic aspects. It explores the progression of language acquisition, phonological development, vocabulary growth, and grammatical complexity in children of this age group. Additionally, the annotation may cover the impact of environmental and cultural influences on speech development, as well as potential challenges such as speech disorders or language delays. The goal is to provide a comprehensive understanding of the multifaceted nature of children's speech development during the junior school years, with implications for educators, parents, and speech-language professionals.